Smart Water Level Detection System - Debby Vivi Lim,; Mohd, Mohd Sabani (Multidisciplinary Applied Research and Innovation, 2026)
Flash floods pose a significant threat in urban areas, particularly in underground parking structures and basements, where rapid water accumulation can lead to severe damage to vehicles, electrical systems, and infrastructure. These events often occur without warning, triggered by heavy rainfall, blocked drainage, or overflowing water sources. To address this challenge, a Smart Water Level Detection System was developed using Internet of Things (IoT) technology to enable real-time monitoring and early warning alerts. The system’s main objective is to detect rising water levels promptly and notify users before critical levels are reached. It integrates two water level sensor switches and an ultrasonic sensor to classify water depth into three categories: Low (0–4 cm), Minimum (4–7 cm), and Maximum (above 8 cm). A NodeMCU ESP8266 microcontroller processes the data collected from the sensors and connects to Wi-Fi for remote communication. Notifications are sent to the user’s smartphone through the Telegram messaging app, while local alerts are provided using a buzzer and OLED screen, offering immediate audible and visual feedback. The system was tested under various simulated water conditions, and the results confirmed accurate detection and reliable responses at all levels. Telegram notifications were received within 1 to 7 seconds depending on the network connection, while the buzzer and OLED screen responded instantly. At the Maximum water level, a high-alert message was triggered alongside buzzer activation. These outcomes validate the system’s efficiency, speed, and suitability for flood-prone environments. By providing both local and remote alerts, this smart system enhances urban flood preparedness, minimizes property damage, and enables faster emergency responses in underground spaces.